Bora Laskin : Bringing Law to Life - Girard, Philip (Book collections on Project MUSE., 2005)
In Bora Laskin, Girard chronicles the life of a man who, at all points of his life, was a fighter for a better Canada: he fought antisemitism, corporate capital, omnipotent university boards, the Law Society of Upper Canada, and his own judicial colleagues in an effort to modernize institutions and re-shape Canadian law.